2016
DOI: 10.1002/chem.201603737
|View full text |Cite
|
Sign up to set email alerts
|

Heteroacene Synthesis through C−S Cross‐Coupling/5‐endodigCyclization

Abstract: Highly efficient, one-step synthesis of sulfur-containing heteroacenes was achieved through palladium-catalyzed C-S cross-coupling of bis-alkynes with thioacetate as hydrogen sulfide surrogate. Heteroacenes consisting of three, five, and seven fused aromatic rings were obtained in a single catalytic step by four-, six-, and eightfold C-S bond formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Recently, Paradies and coworkers 46 reported a highly efficient one-step synthesis of sulfur-containing heteroacenes through palladium-catalyzed C-S cross-coupling of bis-alkynes with thioacetate as a hydrogen sulfide surrogate (Scheme 6). The eight C-S bonds in compound 18 could be synthesized in a single step.…”
Section: S-bridged Lhas Synthesized By Heteroannulationmentioning
confidence: 99%
“…Recently, Paradies and coworkers 46 reported a highly efficient one-step synthesis of sulfur-containing heteroacenes through palladium-catalyzed C-S cross-coupling of bis-alkynes with thioacetate as a hydrogen sulfide surrogate (Scheme 6). The eight C-S bonds in compound 18 could be synthesized in a single step.…”
Section: S-bridged Lhas Synthesized By Heteroannulationmentioning
confidence: 99%
“…We and others have shown that silyl thiol, [ 35 ] thiourea [ 36 ] or potassium thioacetate [ 37 ] offer the unique access to diaryl sulfide derivatives. [ 36,38–42 ]…”
Section: Entrya) X Y Mnb) Mwb) Mw/mn Dpn Equiv 2 Mol% Cat G Mol−1 mentioning
confidence: 99%
“…From earlier studies in our group, we knew that the electron‐rich [Pd( o Tol 3 P) 2 ] complex in combination with the bis(diphenylphosphino)ferrocene ligand (dppf) performed best in the CS cross coupling to form diaryl sulfides. [ 38–40 ] Accordingly, we turned out attention to the optimization of the H 2 S‐surrogate. Whereas thiourea [ 36 ] was inactive in the polycondensation, potassium thioacetate (KSAc, 2 ) was active in the conversion of 1 to polymeric material in the presence of 2 mol% Pd‐catalyst ( Table 1 entries 1–6).…”
Section: Entrya) X Y Mnb) Mwb) Mw/mn Dpn Equiv 2 Mol% Cat G Mol−1 mentioning
confidence: 99%
“…In this regards, we are reporting a new complex of Cu I on modified boehmite nanoparticles as efficient and reusable catalyst for the synthesis of sulfides and diaryl ethers via C−S and C−O cross coupling reactions. Because sulfides and diaryl ethers are starting material for the synthesis of organic compounds, drugs, and biological materials . Also, sulfides are starting materials for the synthesis of sulfoxides and sulfones …”
Section: Introductionmentioning
confidence: 99%
“…Because sulfides and diaryl ethers are starting material for the synthesis of organic compounds, drugs, and biological materials. [46][47][48][49][50][51][52][53][54][55] Also, sulfides are starting materials for the synthesis of sulfoxides and sulfones. [56]…”
Section: Introductionmentioning
confidence: 99%